COMMUNITY EMPOWERMENT OF UNDERGROUND RIVER WATER MANAGEMENT IN PUCUNG VILLAGE, EROMOKO, WONOGIRI, CENTRAL JAVA - - Priyono; Kuswaji Dwi Priyono; Choirul Amin; Arif Jauhari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Pucung village located in the Mount Sewu karst region which is the area near the top with a height of 550 m dpal. The village has a population of 544 families with 4,190 people which more than half (2,350 people) have difficulty getting clean water for daily use. The average income of families is IDR 600,000 per month. When the dry season comes, they have to lose half of their income to buy water. Although since 2013 the lifting of underground river water fromthe Suruh Cave successfully meet the needs of clean water in the Pucung village, however, the distribution of water encountered some constraints, namely: first, the pumping discharge is still a little so that the availability of water for the population is still lacking; and second, the unevendistribution of water causing social problems such as jealousy between residents who already get water to residents who do not get water. Therefore, it is necessary to empowering the communities to manage water resources of the underground river in Pucung so that water needs fulfilled in a fair and equitable. This paper was written from the results of the implementation of the community service program conducted by the Faculty of Geography UMS. Community empowerment is done in the form of trainingand assistance to the community Pucung in managing water resources of the underground river. The issue of lack of water flow can be solved with increased discharge pumping, that is by increasing the capacity of submersible pumps from 1.5 HP to 2 HP. This replacement is able toincrease the pumping discharge from the previous 0.9 liters to 1.2 liters per second per second. The time it takes to fill a tank with a capacity of 12,000 liters using a 1.5 HP pump takes 3 hours 42 minutes, whereas with pump 2 HP takes 2 hours 47 minutes. This means that an increase in the capacity of the pump provides a pumping efficiency. While the problem of uneven distribution of water caused by a less orderly management, resolved by the establishment of a community-based organization named "Tirta Goa Suruh". The establishment of the organization accompanied by the establishment of organizations ranging from discussion,the selection board, management training organization, technical skills training to setup and use vertical work tool and equipment maintenance. Moreover, also conducted training for the youth of Pucung village the introduction of vertical work equipment, their installation and usage, so that they are expected to become the next generation board Tirta Suruh Goa. Keywords: community empowerment, water resource management, underground river